An algorithm for minimizing number of collisions in highways using swarm intelligence - Chaity, Narjis Mostofa (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.